Social computing and social media : participation, user experience, consumer experience, and applications of social computing : 12th International Conference, SCSM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: participation, user experience, consumer experience, and applications of social computing : 12th International Conference, SCSM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part II (2020) - Unknown
No abstract available